ANALISIS DAN PERANCANGAN SISTEM INFORMASI PERSEDIAAN UNTUK MENINGKATKAN PENGENDALIAN INTERNAL (STUDI KASUS PADA PT LOMAX) - Widjijono, Vania Haryanto; Wehartaty, Tineke (Widya Mandala Surabaya Catholic University, 2017)
Inventory of raw materials is one of important asset for companies especially for manufacturing company. Therefore, companies require a good information system and internal control for their own inventory. Without an adequate information sys-tem and internal control, the effectiveness and efficiency of the operation will be hard to achieved. Researcherstried to do research of raw material inventory information system at PT Lomax Surabaya. PT Lomax Surabaya is a manufacturing company that pro-duce machines. The research method conducted is a case study using qualitative data. Data analysis techniquesis started from the evaluation of running raw material inventory information systems, evaluation of user requirements for information systems, eval-uation of internal controls, and the computerized design of raw material inventory information system. Result of this research is the design of raw material inventory information systems that can improve not only internal control but also effectiveness and efficiency of operation of the company. A new system will be able to reduce the risk of recording errors, to improve quality of raw material inventory information and to issue an accurate and timely report.